INTRA-SYSTEM SHIFT ANALYSIS IN THE TRANSLATION OF TOURISM BROCHURE - Putu Diah Kumala Putri (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2023)
This study aims to analyze the shift in translation from translation studies on the translation shiftone on the Prambanan Temple Brochure in translation by Catford (1965). From Bahasa Indonesia asSource English (SL) English target language (TL). This research is a qualitative research method.Intra-system shift was collected by non-participation and using note-taking techniques to collectrelevant data from the Prambanan Temple Tourism Brochure. The analysis used in this research isdescriptive linguistic analysis which tries to explain the standard forms of language. The source ofthe results was that there were 7 intra-system shift data shifts from the translation of the PrambananTemple tourism brochure